2020
DOI: 10.1093/mnras/staa329
|View full text |Cite
|
Sign up to set email alerts
|

On the possibility of through passage of asteroid bodies across the Earth’s atmosphere

Abstract: We have studied the conditions of through passage of asteroids with diameters 200, 100, and 50 m, consisting of three types of materials – iron, stone, and water ice, across the Earth’s atmosphere with a minimum trajectory altitude in the range 10–15 km. The conditions of this passage with a subsequent exit into outer space with the preservation of a substantial fraction of the initial mass have been found. The results obtained support our idea explaining one of the long-standing problems of astronomy – the Tu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…As we have calculated in our work, the radius of this iron asteroid body could have been from 50 to 100 m to avoid disintegration in the atmosphere and to preserve significant part of the initial mass. The most important conclusion of this work is that we have confirmed the realism of the hypothesis that the Tunguska phenomenon can be likely associated with a grazing passage of an iron asteroid body across the Earth's atmosphere with velocities below the fragmentation threshold -20 km/s at the minimum altitude of 10-15 km and its subsequent escape into outer space to the orbit around the Sun (Khrennikov et al 2016(Khrennikov et al , 2020.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…As we have calculated in our work, the radius of this iron asteroid body could have been from 50 to 100 m to avoid disintegration in the atmosphere and to preserve significant part of the initial mass. The most important conclusion of this work is that we have confirmed the realism of the hypothesis that the Tunguska phenomenon can be likely associated with a grazing passage of an iron asteroid body across the Earth's atmosphere with velocities below the fragmentation threshold -20 km/s at the minimum altitude of 10-15 km and its subsequent escape into outer space to the orbit around the Sun (Khrennikov et al 2016(Khrennikov et al , 2020.…”
Section: Discussionsupporting
confidence: 73%
“…The structures of aerodynamic fluxes around a spherical SB as well as around a spherical SB with wedge-shaped notch with formation of vortex structures and stagnation zones in its rear and front parts are shown in our paper (Khrennikov et al 2020) and in Fig. 2.…”
Section: Resultsmentioning
confidence: 79%
See 2 more Smart Citations
“…Recently, Khrenikov et al suggested that it resulted from the passage of an iron asteroid across the Earth's atmosphere. The latter would have hit the upper atmosphere at about 10-15 km and then escaped to the interplanetary space (Khrennikov et al 2020).…”
Section: The 1908 Tunguska Meteoritementioning
confidence: 99%